Modelling a Sustainable Smart City - Botsios, Adrianos Evangelos; Sabbagh, Hasib; Romain, Denis; Theodorakis, Alexandros; Karampelas, Antonios (Open Schools Journal for Open Science, 2022)
This article presents the development of a model of a sustainable smart city. The model demonstrates the use of sustainable forms of energy and incorporates Internet of Things functionalities to simulate energy efficiency, monitoring of air quality, and safety. The city was designed to raise awareness about problems people living in cities face, as well as to inspire relevant technology-based innovative solutions in the context of the Sustainable Development Goal 11 (Sustainable Cities and Communities).